Impact of Culture on Entrepreneurship - Jean Lee (Asian Academy of Management Journal, 1999)
The tendency of certain cultures as a determinant of entrepreneurs has made it intuitively appealing to view culture as a determinant of entrepreneurship. Some cultures, for instance, have been found to be more supportive of entrepreneurial activities than others. However, many of these studies are carried out in the West. So far, little is known of any similar studies that may have been conducted, in the Asian context, to discriminate the cultural values of the entrepreneurs from those of the general population. Since Asians come from a different social-cultural background the results obtained from the western samples may not necessarily be reflective or representative of the values held by their Asian counterparts. It is this particular observation that prompted the present study.